A new species of Shaanxiana (Lepidoptera: Lycaenidae) from southern China - Hsu, Yu-Feng (Zootaxa, 2015)
Shaanxiana australis sp. nov. (Theclinae: Theclini) is described from southern China, representing a new taxon of the genus and a remarkable known geographical range extension of the genus. The larval host plant of S. australis is unknown, but the most likely candidate is Fraxinus chinensis (Oleaceae), because congeneric Shaanxiana takashimai use Fraxinus spp. as larval hosts, and F. chinensis is known to grow at the type locality of S. australis.